Dismissing a Physician for Cause: The Case of Mykal Grady, MD - Winter, Joseph; Agnello, Vincent; Pikas, Bohdan; Ta, Hai (Journal of Management Policy and Practice, 2018)
Sutton Medical Center was just informed through a journalist that the physician they hired was accused of raping two patients. The doctor was given a five year employment contact. In an instant the Center is now going to face bad press and possible legal liability. Students must decide if there is good cause to terminate the physician. Can the Center sue the prior employer for failing to warn the Center? What are the implications to all of the parties involved in the confidential settlement made with the complainant?